Prove that 1+4+9+...+n^2 = n(n+1)(2n+1)/6.

Consider the case n=1. Then 1(1+1)(2*1+1)/6 = 1 = 1^2 and so the claim is true for n=1. Suppose the claim is true for some positive integer n, so that 1+4+9+...+n^2 = n(n+1)(2n+1)/6. Then by the inductive hypothesis 1+4+9+...+n^2 + (n+1)^2 = (1+4+9+...+n^2) + (n+1)^2 = n(n+1)(2n+1)/6 + (n+1)^2                                                                                      = (n+1)(2n^2 + n + 6(n+1))/6                                                                                      = (n+1)(n+2)(2n+3)/6 which is the claim for n+1. As the claim is true for n=1, it's true for all n by induction.

Related Further Mathematics A Level answers

All answers ▸

Solve the equation 3sinh(2x) = 13 - 3e^(2x), answering in the form 0.5ln(k). where k is an integer


How do I convert cartesian coordinates into polar coordinates?


How to multiply and divide by complex numbers


By use of matrices uniquely solve the following system of equations, justifying each step of the calculation: 3x-7y=6, 5y-2x=-3.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences